A Correlational Study Between Vocabulary Mastery, Studentâs English Interest, And Studentâs English Achievement - Mega, Iful Rahmawati; Rais, A. Dahlan; Asib, Abdul (JoLLIET, 2015)
The study is aimed to find out the correlation between vocabulary mastery and studentâs English interestÂ toward studentâs English achievement of the second grade students of SMPN 3 Sukoharjo; both partially and simultaneously. This study used a test, a questionnaire, and a documentation to collect the data. The population of the study is all of the second grade students while the sample is 50 students taken by cluster random sampling technique. The techniques used to analyze the data are simple and multiple correlation and regression by using SPSS 17. The results of the study show that there is a positive correlation between vocabulary mastery and studentâs English interest toward studentâs English achievement, both partially and simultaneously. The positive correlation indicates that vocabulary mastery and studentâs English interest tend to go up or to go down together with studentâs English achievement.